Investigation of celiac disease according to Marsh classification in childhood (Bangladesh Journal of Medical Science, 2017)
Background: Celiac disease (CD) is an autoimmune disorder of the small intestine related to gluten. CD is diagnosed by the evaluation of histologic findings according to the Marsh classification.Objectives: To evaluate the clinical and laboratory differences of CD according to Marsh classification.Patients and method: The records of ?Marsh 2 histologically diagnosed 132 cases were evaluated.Results: It was determined that 7(5.3%) cases were Marsh 2, 32(24.2%) were Marsh 3a, 73(55.3%) were Marsh 3b, and 20(15.1%) were Marsh 3c. Vomiting in Marsh 2 was significantly lower than Marsh 3b and Marsh 3c (respectively, 14.3% vs. 56.9%, p=0.029; and 14.3% vs. 75%, p=0.005). Hemoglobin was significantly higher in Marsh 2 than Marsh 3b and Marsh 3c (respectively, 11.9±1.7 vs. 10.5±1.6 g/dl, p=0.038 and; 11.9±1.7 vs. 9.8±1.6 g/dl, p=0.005). Positive detection ratio for tTG IgA was significantly lower in Marsh 2 than Marsh 3a, Marsh 3b and Marsh 3c (respectively, 66.7% vs. 100%, p